Bungo Krinok Music from Local to Global - Mahdi Bahar; Hartati M; Indra Gunawan; Fatonah; Uswan Hasan; Zulkarnain (PT Inovasi Pratama Internasional, 2023)
Bungo Krinok music is the result of research funded by LPDP for two years (2020 - 2023) in the form of a prototype of a new form of engineered music antithesis to the traditional krinok singing genre of the people of Bungo Regency, Jambi Province. The singing of krinok is accompanied by violin or the supporting community calls piul. The structure of the permanent krinok music composition is used as the main basis and the static framework in music engineering / creation becomes the form (genre) of music composition